2017
DOI: 10.56093/ijas.v87i10.74972
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis for various agromorphological and quality traits in bread wheat (Triticum aestivum)

Abstract: A study was made to estimate gene action and combining ability effects involving 10 diverse parents and their 45 F1s (half diallel approach) developed and evaluated during 2012-13 and 2013-14 crop seasons, respectively. The general combining ability (GCA) estimates for bread wheat (Triticum aestivum L.) genotypes namely, HD 2967 (days to maturity, plant height); DBW 90 (plant height, spikelets/spike, grains/spike, grain yield); HD 2824 (plant height, spikelets/spike); HD 3095 (spikelets/spike, grains/spike, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
4
1
0
Order By: Relevance
“…A perusal of Table 2 showed high estimates of heritability for tillers per plant (44.74), harvest index (34.45), grain yield per plant (31.51) and 1000-grain weight (30.54). Above results are in close agreement with the findings of Maurya et al [15]; Meena et al [16] and Mecha et al [17].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…A perusal of Table 2 showed high estimates of heritability for tillers per plant (44.74), harvest index (34.45), grain yield per plant (31.51) and 1000-grain weight (30.54). Above results are in close agreement with the findings of Maurya et al [15]; Meena et al [16] and Mecha et al [17].…”
Section: Resultssupporting
confidence: 93%
“…Analysis of variance for the design showed the significant difference between the genotypes for the characters such plant height (45.94), tillers per plant (1.34), 1000-grain weight (3.48), biological yield per plant (31.14), harvest index (13.96) and grain yield per plant (3.58). Similar findings have also been reported by Rangare et al [13]; Maan and Yadav 2010; Zine et al 2013; Verma et al [8], Yadav et al [14], Maurya et al [15]; Meena et al [16] and Mecha et al [17].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These findings suggested that the additive gene effect plays a major role in quantitative expression of these traits. Similar findings were reported by Ljubicic et al, 2016 for number of grains per spike, Usman et al, 2013 andKumar et al, 2013 for spike length. For the improvement of these traits selection would be effective in early segregating generations.…”
Section: Resultssupporting
confidence: 89%
“…Many benefits from bed planting have been reported by Kumar et al (2007) and Holland et al (2007). Likewise, there are some benefits of this planting system such as low seed rate, reduction of crop lodging, better control of excess water in heavy soil conditions (Sayre and Ramos 1997).…”
Section: -Economic Evaluationmentioning
confidence: 99%